2014
DOI: 10.1007/s00464-014-3977-9
|View full text |Cite
|
Sign up to set email alerts
|

Yield of colonoscopy after recent CT-proven uncomplicated acute diverticulitis: a comparative cohort study

Abstract: ACN detection does not differ significantly between patients with recent uncomplicated diverticulitis and average risk screening participants. Routine follow-up colonoscopy after primary CT-proven uncomplicated left-sided acute diverticulitis can be omitted; these patients can participate in CRC screening programs. Follow-up colonoscopy may be beneficial when targeted at high-risk patients, but such an approach first needs prospective evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 46 publications
5
61
0
Order By: Relevance
“…The authors draw similar conclusions compared to our previous study. Follow-up with colonoscopy may be beneficial only for high-risk patients [22]. Several other studies regarding the necessity of diagnostic colonoscopy after proven diverticulitis are in line with our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The authors draw similar conclusions compared to our previous study. Follow-up with colonoscopy may be beneficial only for high-risk patients [22]. Several other studies regarding the necessity of diagnostic colonoscopy after proven diverticulitis are in line with our study.…”
Section: Discussionsupporting
confidence: 89%
“…In the case of alarm symptoms, a colonoscopy does appear to be indicated to rule out CRC [8,21]. This is in line with the study of Daniels et al [22] who showed that detection of advanced colonic neoplasia by colonoscopy after CTproven uncomplicated acute diverticulitis is comparable to randomly picked asymptomatic CRC screening participants. The authors draw similar conclusions compared to our previous study.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, a study of 80 follow-up endoscopies detected no CRC 8. However, three recent large studies reported higher CRC detection rates of 2.1%,10 4.3%,16 and 2.2% 14. These studies followed up 319, 394, and 402 patients by endoscopy, respectively, the results of which are similar to the overall CRC detection rate in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The largest study performed included 2,821,392 screening colonoscopies and found a CRC prevalence of 0.9% [32] . Furthermore, recently published literature has shown that the prevalence of AA, ACN, and CCR did not significantly differ between patients with recent uncomplicated diverticulitis and average-risk screening participants [36][37][38][39][40] .…”
Section: Discussionmentioning
confidence: 90%